Home » Functions

Tag: Functions

Find functions satisfying given conditions

Find functions satisfying the given conditions in each of the following cases.

  1. \displaystyle{ f'(x^2) = \frac{1}{x} } for x> 0 and f(1) = 1.
  2. \displaystyle{ f'(\sin^2 x)  = \cos^2 x} for all x, and f(1) = 1.
  3. \displaystyle{ f'(\sin x) = \cos^2 x} for all x and f(1) = 1.
  4. \displaystyle{ f'(\log x) = \begin{cases} 1 & \text{for } 0 < x \leq 1, \\ x & \text{for } x > 1, \end{cases}} and f(0) = 0.

  1. We make the substitution t = x^2. Since x > 0 this gives us x = \sqrt{t}. Therefore,

        \begin{align*}  f'(x^2) = \frac{1}{x} && \implies && f'(t) &= \frac{1}{\sqrt{t}} \\[9pt]  && \implies && \int f'(t) \, dt &= \int \frac{1}{\sqrt{t}} \, dt \\[9pt]  && \implies && f(t) &= 2 \sqrt{t} + C. \end{align*}

    Since we are given f(1) = 1 we can solve for C,

        \[ 1 = f(1) = 2 \sqrt{1} + C \quad \implies \quad C = -1. \]

    Therefore,

        \[ f(t) = 2 \sqrt{t} - 1. \]

  2. We make the substitution t = \sin^2 x. Since \sin^2 x + \cos^2 x = 1 we then have \cos^2 x = 1 - t. Therefore,

        \begin{align*}  f'(\sin^2 x) = \cos^2 x && \implies && f'(t) &= 1-t \\[9pt]  && \implies && \int f'(t) \, dt &= \int (1-t) \, dt \\[9pt]  && \implies && f(t) &= t - \frac{t^2}{2} + C.  \end{align*}

    Since we are given that f(1) = 1 we can solve for C,

        \[ 1 = f(1) = 1 - \frac{1}{2} + C \quad \implies \quad C = \frac{1}{2}. \]

    Therefore,

        \[ f(t) = t - \frac{t^2}{2} + \frac{1}{2}. \]

    This formula is valid for 0 \leq t \leq 1 since t = \sin^2 x and 0 \leq \sin^2 x \leq 1 for all x.

  3. We make the substitution t = \sin x. Since \sin^2 x + \cos^2 x =1 we then have \cos^2 x = 1 - t^2. So,

        \begin{align*}  f'(\sin x) = \cos^2 x && \implies && f'(t) &= 1-t^2 \\[9pt]  && \implies && \int f'(t) \, dt &= \int (1-t^2) \, dt \\[9pt]  && \implies && f(t) &= t - \frac{t^3}{3} + C. \end{align*}

    Since we are given that f(1) = 1 we can solve for C,

        \[ 1 = f(1) = 1 - \frac{1}{3} + C \quad \implies \quad C = \frac{1}{3}. \]

    Therefore,

        \[ f(t) = t - \frac{t^3}{3} + \frac{1}{3}. \]

    This is valid for |t| \leq 1 since t = \sin x and -1 \leq \sin x \leq 1 for all x.

  4. We make the substitution t = \log x. Then, x = e^t and so we have

        \[ f'(\log x) = \begin{cases} 1 & \text{for } 0 < x \leq 1, \\ x & \text{for } x > 1, \end{cases} \quad \implies \quad f'(t) = \begin{cases} 1 & \text{for } 0 < x \leq 1, \\ e^t & \text{for } x > 1. \end{cases}\]

    So, we consider the two cases separately. If 0 < x \leq 1 then we have t < 0 and

        \[ f'(t) = 1 \quad \implies \quad \int f'(t) \, dt = \int 1 \, dt \quad \implies \quad f(t) = t + C. \]

    If x > 1 then we have t \geq 0 and

        \[ f'(t) = e^t \quad \implies \quad \int f'(t) \,dt = \int e^t \, dt \quad \implies \quad f(t) = e^t + C. \]

    Therefore, we have the function

        \[ f(t) = \begin{cases} t + C & \text{if } t < 0, \\ e^t + C & \text{if } t \geq 0. \end{cases} \]

    Now, to solve for C we use the condition that f(0) = 0. (Here we’re going to assume we want to make the function continuous at t = 0, i.e., that the two pieces of this piecewise definition take the same value at 0 so that the limits from the left and right would be equal.) Therefore, we have

        \[ 0 = f(0) = 0 + C \quad \implies \quad C = 0 \]

    and

        \[ 0 = f(0) = e^0 + C \quad \implies \quad C = -1.\]

    Thus, the function is given by

        \[ f(t) = \begin{cases} t & \text{if } t < 0, \\ e^t - 1 & \text{if } t \geq 0. \end{cases} \]

Prove that different functions may have the same average

Let f be a continuous, strictly monotonic function on \mathbb{R}_{>0} with inverse g, and let a_1 < a_2 < \cdots < a_n be given positive real numbers. Then define,

    \[ M_f = g \left( \frac{1}{n} \sum_{i=1}^n f(a_i) \right). \]

This M_f is called the mean of a_1, \ldots, a_n with respect to f. (When f(x) = x^p for p \neq 0, this coincides with the pth power mean from this exercise).

Show that if h(x) = af(x) + b with a \neq 0, then M_h = M_f.


Proof. Let h(x) = af(x) + b with a \neq 0. Then, h has an inverse since it is strictly monotonic (since it is the composition of f and the linear function ax+b, both of which are strictly monotonic for a \neq 0). Its inverse is given by

    \[ h^{-1}(x) = f^{-1} \left( \frac{x-b}{a} \right). \]

So,

    \begin{align*}  M_h &= h^{-1} \left( \frac{1}{n} \sum_{i=1}^n h(a_i) \right) \\  &= h^{-1} \left( \frac{1}{n} \sum_{i=1}^n (af(a_i) + b) \right) \\  &= h^{-1} \left( \frac{a}{n} \left(\sum_{i=1}^n f(a_i)\right) + b \right)\\  &= f^{-1} \left(\frac{\frac{a}{n} \left(\sum_{i=1}^n f(a_i)\right) + b - b}{a} \right)\\  &= g \left( \frac{1}{n} \sum_{i=1}^n f(a_i) \right) \\  &= M_f. \qquad \blacksquare \end{align*}

Show the mean of a strictly monotonic function lies in an interval

Let f be a continuous, strictly monotonic function on \mathbb{R}_{>0} with inverse g, and let a_1 < a_2 < \cdots < a_n be given positive real numbers. Then define,

    \[ M_f = g \left( \frac{1}{n} \sum_{i=1}^n f(a_i) \right). \]

This M_f is called the mean of a_1, \ldots, a_n with respect to f. (When f(x) = x^p for p \neq 0, this coincides with the pth power mean from this exercise).

Show that

    \[ a_1 < M_f < a_n. \]


Proof. Since f is strictly monotonic on the positive real axis and a_1 < a_2 < \cdots < a_n are n positive reals, we know f is strictly increasing or strictly decreasing, and correspondingly we have,

    \[ f(a_1) < f(a_2) < \cdots < f(a_n) \qquad \text{or} \qquad f(a_1) > f(a_2) > \cdots > f(a_n). \]

First, assume f is striclty increasing, then

    \[ f(a_1) < \cdots < f(a_n) \quad \implies \quad \frac{1}{n} \sum_{i=1}^n f(a_1) < \frac{1}{n} \sum_{i=1}^n f(a_i) < \frac{1}{n} \sum_{i=1}^n f(a_n). \]

Since f is strictly increasing so is its inverse g (by Apostol’s Theorem 3.10); thus, we have

    \begin{align*}  &g \left( \frac{1}{n} \sum_{i=1}^n f(a_1) \right) < g \left( \frac{1}{n} \sum_{i=1}^n f(a_i) \right) < g \left( \frac{1}{n} \sum_{i=1}^n f(a_n) \right) \\[8pt]  &\implies \quad g(f(a_1)) < M_f < g(f(a_n)) \\  &\implies \quad a_1 < M_f < a_n. \end{align*}

If f is strictly decreasing then

    \begin{align*}  & f(a_1) > \cdots > f(a_n) \\[8pt] \implies & \frac{1}{n} \sum_{i=1}^n f(a_1) > \frac{1}{n} \sum_{i=1}^n f(a_i) > \frac{1}{n} \sum_{i=1}^n \\[8pt] \implies & g\left( \frac{1}{n} \sum_{i=1}^n f(a_1) \right) < g \left( \frac{1}{n} \sum_{i=1}^n f(a_i) \right) < g \left( \sum_{i=1}^n f(a_n) \right) \\[8pt] \intertext{(where the inequalities reverse since $f$ decreasing implies its inverse, $g$, is also decreasing)} \implies & a_1 < M_f < a_n. \qquad \blacksquare \end{align*}

Formula for counting lattice points in the ordinate set of a function

For a nonnegative function f defined on an interval [a,b] define the set

    \[ S = \{ (x,y) \mid a \leq x \leq b, \ 0 < y \leq f(x) \}. \]

(i.e., the region enclosed by the graph of the function and the x-axis between the vertical lines at x=a and x=b). Then prove

    \[ \text{\# of lattice points in } S = \sum_{n=a}^b [f(n)], \]

where [f(n)] is the greatest integer less than or equal to f(n).


We can help ourselves by drawing a picture to get a good idea of what is going on, then turn that intuition into something more rigorous. The picture is as follows:

Rendered by QuickLaTeX.com

In the picture, we can see the number of lattice points in the ordinate set of f(x) (not including the x-axis since the question stipulates S contains the points 0 < y \leq f(x)). At each integer between a and b, we count the number of lattice points beneath [f(x)], the greatest integer less than or equal to f(x). Then we need to turn this intuition from the picture into a proof:

Proof. Let n \in \mathbb{Z} with a \leq n < b. We know such an n exists since a,b \in \mathbb{Z} with a < b. Then, the number of lattice points in S with first element n is the number of integers y such that 0 < y \leq f(n). But, by definition, this is [f(n)] (the greatest integer less than or equal to f(n)). Summing over all integers n, \ a \leq n \leq b we have,

    \[ \text{\# of lattice points in } S = \sum_{n=a}^b [ f(n) ]. \qquad \blacksquare\]

Prove some properties of the greatest integer function

For any x \in \mathbb{R} we denote the greatest integer less than or equal to x by [x]. Prove the following properties of the function [x]:

  1. [x+n] = [x] + n for any integer n.
  2. [-x] = \displaystyle{\begin{cases}  -[x] & \text{if } x \text{ is an integer,} \\ -[x]-1 & \text{otherwise.} \end{cases}}
  3. [x+y] = [x]+[y] or [x]+[y]+1.
  4. [2x] = [x] + \left[ x + \frac{1}{2} \right].
  5. [3x] = [x] + \left[ x + \frac{1}{3} \right] + \left[ x + \frac{2}{3} \right].

  1. Proof. Let [x+n] = m for some integer m. Then,

        \begin{align*}  m \leq x+n < m+1 &&\implies  && m-n &\leq x < m-n+1 \\ &&\implies && [x] &= m-n \\ &&\implies && [x] + n &=  m. \end{align*}

    But, we defined m=[x+n]. Thus, [x+n] = [x] + n for any n \in \mathbb{Z}. \qquad \blacksquare

  2. Proof. If x \in \mathbb{Z}, then x = n for some n \in \mathbb{Z}. Hence, [x]=n and

        \[ -x=-n \quad \implies \quad [-x]=-n \quad \implies \quad [-x]=-[x]. \]

    On the other hand, if x \notin \mathbb{Z}, then let [x] = n. This gives us,

        \begin{align*}  n \leq x < n+1 &&\implies && -n-1 &< -x < n &(n \neq x \text{ since } x \notin \mathbb{Z}) \\ &&\implies && [-x] &= -n-1 = -[x]-1. \qquad \blacksquare \end{align*}

  3. Proof. Let [x] = m and [y] = n, then we have

        \[ m \leq x < m+1 \qquad \text{and} \qquad n \leq y < n+1. \]

    So, adding, we obtain,

        \[ m+n \leq x+y < m+n+2. \]

    Thus,

        \[ [x+y] = m+n = [x] + [y] \qquad \text{or} \qquad [x+y] = m+n+1 = [x] + [y] + 1. \qquad \blacksquare\]

  4. Proof. By part (c) we have,

        \[ [2x] = [x+x] = [x] + [x] \qquad \text{or} \qquad [x] + [x] + 1. \]

    If [2x] = [x] + [x], then let [x] = n,

        \begin{align*}  && [2x] &= 2n \\ \implies && 2n &\leq 2x < 2n+1 \\ \implies && n &\leq x < n + \frac{1}{2} \\ \implies && n &\leq x + \frac{1}{2} < n+1 \\ \implies && \left[ x + \frac{1}{2} \right] &=n . \end{align*}

    Thus, [2x] = 2n = n+n = [x] + \left[ x + \frac{1}{2} \right].
    On the other hand, if [2x] = [x] + [x] + 1, then let [x] = n, and

        \begin{align*}   && [2x] &= 2n+1 \\  \implies && 2n+1 &\leq 2x < 2n+2 \\  \implies && n+\frac{1}{2} &\leq x < n+1 \\  \implies && n +1 &\leq x + \frac{1}{2} <  n+2 \\  \implies && \left[ x + \frac{1}{2} \right] &= n+1. \end{align*}

    Thus, [2x] = n+n+1 = [x] + \left[ x + \frac{1}{2} \right]. \qquad \blacksquare

  5. Proof. By part (c) we have

        \[ [3x] = [x+x+x] = [x+x] + [x] \qquad \text{or} \qquad [x+x]+[x] + 1. \]

    And,

        \[ [x+x] = [x] + [x] \qquad \text{or} \qquad [x]+[x]+1. \]

    So, putting these together we have,

        \[ [3x] = [x]+[x]+[x], \qquad \text{or} \qquad [x]+[x]+[x]+1, \qquad \text{or} \qquad [x]+[x]+[x]+2. \]

    If [3x] = [x] + [x] + [x], then, let [x] = n, so

        \begin{align*} && 3n &\leq 3x < 3n+1 \\ \implies && n &\leq x < n + \frac{1}{3} \\ \implies && n &\leq x + \frac{1}{3} < n+1 & \text{and}&& n &\leq x+\frac{2}{3} < n+1 \\ \implies && [x] &= \left[ x+ \frac{1}{3} \right] = \left[ x+ \frac{2}{3} \right] = n.  \end{align*}

    Thus, [3x] = 3n = [x] + \left[ x + \frac{1}{3} \right] + \left[ x + \frac{2}{3} \right].
    Next, if [3x] = [x] + [x] + [x] + 1, then let [x] = n, giving us,

        \begin{align*}  && 3n+1 &\leq 3x < 3n+1 \\ \implies && n + \frac{1}{3} &\leq x < n + \frac{2}{3} \\ \implies && n + \frac{1}{3} & \leq x + \frac{1}{3} < n+1 &\implies \quad \left[ x + \frac{1}{3} \right] &=n \\ \text{and}, \ \implies && n + 1 &\leq x + \frac{2}{3} < n+2 &\implies \quad \left[ x + \frac{2}{3} \right] &= n+1. \end{align*}

    Thus,

        \[ [3x] = 3n+1  \quad \implies \quad [3x] = [x] + \left[ x + \frac{1}{3} \right] + \left[ x + \frac{2}{3} \right]. \]

    Finally, if [3x] = [x] + [x] + [x] + 2, then let [x] = n, and we have

        \begin{align*} && 3n+2 &\leq 3x < 3n+3 \\ \implies && n+\frac{2}{3} &\leq x < n+1 \\ \implies && n+1 &\leq x+\frac{1}{3} < n+2 & \text{and} && n+1 \leq x+\frac{2}{3} < n+2.  \end{align*}

    So,

        \[ [3x] = 3n+2 = [x] + \left[ x + \frac{1}{3} \right] + \left[ x + \frac{2}{3} \right]. \qquad \blacksquare \]

Draw the graphs of some functions

Draw the graphs of the functions defined below on the interval [-2,2], and if it is a step function find a partition P such that the function is constant on the open subintervals of P.

  1. f(x) = x + [x].
  2. f(x) = x - [x].
  3. f(x) = [-x].
  4. f(x) = 2[x].
  5. f(x) = \left[x+\frac{1}{2} \right].
  6. f(x) = [x] + \left[ x+ \frac{1}{2} \right].

  1. This is not a step function. The graph is below.

    Rendered by QuickLaTeX.com

  2. This is not a step function. The graph is below.

    Rendered by QuickLaTeX.com

  3. This is a step function and it is constant on the open subintervals of the partition, P = \{ -2,-1,0,1,2 \}. The graph is below.

    Rendered by QuickLaTeX.com

  4. This is a step function and it is constant on the open subintervals of the partition, P = \{ -2,-1,0,1,2 \}. The graph is below.

    Rendered by QuickLaTeX.com

  5. This is a step function and it is constant on the open subintervals of the partition, P = \left\{ -2,-\frac{3}{2},-\frac{1}{2},\frac{1}{2},\frac{3}{2},2 \right\}. The graph is below.

    Rendered by QuickLaTeX.com

  6. This is a step function and it is constant on the open subintervals of the partition, P = \left\{ -2,-\frac{3}{2},-1,-\frac{1}{2},0,\frac{1}{2},1,\frac{3}{2},2 \right\}. The graph is below.

    Rendered by QuickLaTeX.com